2020
DOI: 10.1680/jgeot.18.pisa.003
|View full text |Cite
|
Sign up to set email alerts
|

Monotonic laterally loaded pile testing in a stiff glacial clay till at Cowden

Abstract: This paper describes the results obtained from a field testing campaign on laterally loaded monopiles conducted at Cowden, UK, where the soil consists principally of a heavily overconsolidated glacial till. These tests formed part of the PISA project on the development of improved design methods for monopile foundations for offshore wind turbines. Results obtained for monotonic loading tests on piles of three different diameters (0•273 m, 0•762 m and 2•0 m) are presented. The piles had length-todiameter ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 14 publications
(34 reference statements)
0
25
0
Order By: Relevance
“…This section describes the calibration of the PIMS model to monotonic and cyclic laboratory test data for two overconsolidated clays, accompanied by 3D FEA of monopile foundations subjected to monotonic and cyclic lateral loading. The Bolders Bank formation is also the main geotechnical unit at the Cowden test site, where laterally loaded pile tests were conducted during the PISA research project (Byrne et al, 2019). Triaxial test data from the Cowden site (Zdravković et al, 2019) were found to be broadly consistent with the Fugro data set employed to calibrate the PIMS model.…”
Section: Overview Of Application Examplesmentioning
confidence: 72%
See 1 more Smart Citation
“…This section describes the calibration of the PIMS model to monotonic and cyclic laboratory test data for two overconsolidated clays, accompanied by 3D FEA of monopile foundations subjected to monotonic and cyclic lateral loading. The Bolders Bank formation is also the main geotechnical unit at the Cowden test site, where laterally loaded pile tests were conducted during the PISA research project (Byrne et al, 2019). Triaxial test data from the Cowden site (Zdravković et al, 2019) were found to be broadly consistent with the Fugro data set employed to calibrate the PIMS model.…”
Section: Overview Of Application Examplesmentioning
confidence: 72%
“…Triaxial test data from the Cowden site (Zdravković et al, 2019) were found to be broadly consistent with the Fugro data set employed to calibrate the PIMS model. On the basis of this observation, several of the PISA pile tests were analysed using the calibrated PIMS model and the computed results compared with the field data (Byrne et al, 2019). Fig.…”
Section: Overview Of Application Examplesmentioning
confidence: 99%
“…The main purpose of the study was to develop a 3D FE model to, first, design the PISA test piles at Cowden from the predicted responses of the 3D FE model, and, second, to validate the 3D FE model by comparing these predictions with the field test results obtained subsequently. Two pile diameters ( = 0.762 m and = 2.0 m) and three length-to-diameter ratios ( = 3 ⁄ , 5.25 and 10) were used for field testing, with a monotonic horizontal load applied at the top of a 10 m high steel tubular extension mounted on the pile heads (see Byrne et al, 2019a). The problem was discretised into the FE mesh shown in Figure 10.…”
Section: Stiffnessmentioning
confidence: 99%
“…Phoon and Tang (2019a) have recently combined two databases to study capacity of static load tests on steel piles founded in various soil types. The joint industry research project Pile-Soil Analysis (PISA) has produced significant results and reports detailing premium quality site data (Burd et al 2020a(Burd et al , 2020bByrne et al 2017Byrne et al , 2020Zdravković et al 2020aZdravković et al , 2020b.…”
Section: Introductionmentioning
confidence: 99%